2003
DOI: 10.1046/j.1523-1755.2003.00028.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel HIV-1 transgenic rat model of childhood HIV-1–associated nephropathy

Abstract: These data support the notion that HIV-1 plays a direct role in the pathogenesis of HIVAN, by affecting the function and growth of renal epithelial cells, inducing the recruitment of mononuclear cells, and accumulating bFGF in the kidney, even in the absence of viral replication. These rats may provide an excellent model system to study the pathogenesis of childhood HIVAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 44 publications
4
60
0
Order By: Relevance
“…The transgenic Tg26 mouse expressed seven of 15 HIV-1 gene products and developed proteinuria and collapsing FSGS with extensive tubulointerstitial damage that resembles the disease that is seen in humans (64). A similar rat model that replicates the phenotype of a transgenic mouse has also been developed (65,66). These experiments convincingly demonstrated that the HIV-1 gene products are important in the pathogenesis of HIVAN.…”
Section: Genetic Susceptibility and Hivansupporting
confidence: 50%
“…The transgenic Tg26 mouse expressed seven of 15 HIV-1 gene products and developed proteinuria and collapsing FSGS with extensive tubulointerstitial damage that resembles the disease that is seen in humans (64). A similar rat model that replicates the phenotype of a transgenic mouse has also been developed (65,66). These experiments convincingly demonstrated that the HIV-1 gene products are important in the pathogenesis of HIVAN.…”
Section: Genetic Susceptibility and Hivansupporting
confidence: 50%
“…9,[41][42][43][44][45][46] It is reasonable to conclude that DNC plays a mechanistic role in mitochondrial defects from thymidine analog-based HAART. Intramitochondrial abundance of phosphorylated and unphosphorylated native nucleo- sides and NRTIs affects inhibition mtDNA replication at the level of the nucleotide substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble gp120 can induce apoptosis in lymphocytes, 12 but also in neurones, [24][25][26][27] cardiomyocytes, 17,28 kidney epithelial cells 29,30 and hepatocytes. 31 These potent cytotoxic effects have been implicated in the HIV-1-induced lymphodepletion, HIV-associated dementia (also called HIV encephalitis or neuro-AIDS), AIDS-cardiomyopathy, as well as AIDS associated nephropathy and hepatopathy.…”
Section: Cell Killing By Soluble Gp120mentioning
confidence: 99%